Analysis Of Innovation “Puber Anak Melania” In Acceleration Of Birth Certificate Ownership For Children 0-18 Years In The Dinas Kependudukan Dan Pencatatan Sipil Kota Payakumbuh Using Grounded Theory - Gusmeri, Gusmeri; Desmalina, Desmalina; Harsemarozi, Harsemarozi; Heikal, Jerry (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
“Puber Anak Melania” is a Program of the Payakumbuh City Government, in this case the Population and Civil Registration Office as a new innovation in providing convenience in obtaining family cards, birth certificates and baby identity cards for the people of Payakumbuh City. It is an acronym for "Pulang Bersalin Anak mendapat Akta Lahir dan Identitas Anak". This innovation program is a collaborative program with the Payakumbuh City Population and Civil Registration Office with RSKIA, Community Health Centers and independent practicing midwives throughout Payakumbuh City for mothers who give birth in health facilities in Payakumbuh City. The purpose of this study was to determine the effectiveness of Puber Anak Melania service innovation program in accelerating birth certificate ownership in Payakumbuh City, the inhibiting factors and to find out the efforts made by the Payakumbuh Population and Civil Registration Office using a grounded theory approach. Based on the research results, the authors concluded that the implementation of Puber Anak Melania Service innovation was quite effective. Even though there were obstacles such as the parents had not prepared the documents and requirements for issuing a birth certificate, the parents' data and documents had not been valid, and the baby's name had not been prepared by the parents so that the issuance of the birth certificate could not be processed. "Puber Anak Melania" is a Program of the Payakumbuh City Government, in this case the Population and Civil Registration Office as an innovation in providing convenience in obtaining family cards, birth certificates and baby identity cards for the people of Payakumbuh City. It is an acronym for " Pulang Bersalin Anak mendapat Akta Lahir dan Identitas Anak". This innovation program is a collaborative program with the Payakumbuh City Population and Civil Registration Office with RSKIA, Community Health Centers and independent practicing midwives throughout Payakumbuh City for mothers who give birth in health facilities in Payakumbuh City. The purpose of this study was to determine the supporting and inhibiting factors for Melania's Child Development service innovation program in accelerating birth certificate ownership in Payakumbuh City using a grounded theory approach. Based on the research results, the authors conclude that the implementation of the service innovation "Melania Childhood Puberty" has been going well but the results have not been optimal, namely there are obstacles such as documents and requirements for issuing birth certificates that have not been prepared by parents, data and documents of parents are not yet valid, and names the parents had not prepared the baby so that the issuance of the birth certificate could not be processed.